Myelin water fraction decrease in individuals with chronic mild traumatic brain injury and persistent symptoms. Issue 4 (April 2021) - Russell-Schulz, Bretta; Vavasour, Irene M.; Zhang, Jing; MacKay, Alex L.; Purcell, Victoria; Muller, Angela M.; Brucar, Leyla R.; Torres, Ivan J.; Panenka, William J.; Virji-Babul, Naznin
Abstract: The diffuse and continually evolving secondary changes after mild traumatic brain injury (mTBI) make it challenging to assess alterations in brain-behaviour relationships. In this study we used myelin water imaging to evaluate changes in myelin water fraction (MWF) in individuals with chronic mTBI and persistent symptoms and measured their cognitive status using the NIH Toolbox Cognitive Battery. Fifteen adults with mTBI with persistent symptoms and twelve age, gender and education matched healthy controls took part in this study. We found a significant decrease in global white matter MWF in patients compared to the healthy controls. Significantly lower MWF was evident in most white matter region of interest (ROIs) examined including the corpus callosum (separated into genu, body and splenium), minor forceps, right anterior thalamic radiation, left inferior longitudinal fasciculus; and right and left superior longitudinal fasciculus and corticospinal tract. Although patients showed lower cognitive functioning, no significant correlations were found between MWF and cognitive measures. These results suggest that individuals with chronic mTBI who have persistent symptoms have reduced MWF. Abstract : magnetic resonance imaging; mild traumatic brain injury; cognition; myelin water fraction; chronic injury